Study on the Interaction Mechanism Between Soybean Protein Isolates and Lemon Flavor: Isomerization and Degradation of Citral - Guo, Jun; Xu, Jicheng; Chen, Jie (Frontiers in Nutrition, 2022)
By headspace solid-phase microextraction/gas chromatography–mass spectrometry, The effects of 1% (w/v) alcohol washings of the SPI, native SPI, as well as the thermal denaturation of SPI on low concentration (24 μm) of citral was studied in aqueous. The results shows that the SPI could catalyze citral isomerization and yield methyl heptenone and acetaldehyde by inverse aldol condensation degradation. 3-Hydroxycitronelloal was formed as an intermediate in this reaction. The catalytic efficiency of the alcohol-washed protein was higher than that of native soybean protein isolates, whereas the catalytic efficiency of heat-denatured soybean protein isolates was the lowest. Additionally, we found that the catalytic efficiency increased as the pH increased. The catalytic efficiency of 7S was greater than that of 11S. Based on the findings from our study, the use of citral and its isomers in food has been discussed.